Lithuanian insitution at the begining of German -USSR war: features of their activity, competence and position toward ethnical minorities - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2003)
At the outbreak of the German–Soviet War, the Lithuanian Provisional Government (LLV) was established in Kaunas. It attempted to restore the economic order, legal system, and local self–government that existed before the Soviet occupation. However, the jurisdiction of the LLV did not cover the whole of Lithuania, as the occupation of the country by different units of the German army and the establishment of two military field command units in Kaunas and in Vilnius inevitably led to the creation of two administrative centres of civil life. Thus, when Vilnius and eastern Lithuania came under the jurisdiction of the other field commandant, the second most important Lithuanian governmental institution, the Citizens’ Committee of the City and Region of Vilnius, was established there. This article presents the circumstances of its establishment, its activities, and its attitude towards ethnic minorities.